New enzymes with potential for PET surface modification - Fischer-Colbrie, Gudrun (2004)
This work describes newly isolated organisms and their potential to modify the surface of polyethylene terephthalate (PET). Out of the different screening processes, four bacterial and five fungal strains were isolated. A PET model substrate was synthesized (bis (benzoyloxyethyl) terephthalate) and used in the screening process, mimicking the polymer in its crucial properties and having the advantage of defined hydrolysis products. On this model substrate, extracellular enzyme preparations from the isolated microorganisms showed a maximum activity of 8.54 nkat/L. All enzyme preparations showed esterase activity on p-nitrophenyl-acetate while no activity was found on p-nitrophenyl decanoate or p-nitrophenyl palmitate. Increased hydrophilicity of PET fabrics after enzyme treatment was found based on rising height and water dissipation measurements.